P037: The impact of fever on corrected QT interval in a general emergency department population. (2nd June 2016) - Drew, D.; Baranchuk, A.; Brison, R.J.
Abstract : Introduction: Fever is one of the most common reasons for presentation to the emergency department (ED). Interestingly, a number of small studies suggest that fever may function as a modulator of the QT interval in healthy individuals and an arrhythmogenic trigger in patients with occult congenital QT abnormalities. The objective of this study was to explore whether presence of fever adversely affects the QT interval, and whether medications known to prolong this interval affect any association found.Methods: We performed a retrospective, single center study identifying patients (age > 18 years) presenting to the ED with fever (temperature > 38.0 °C) between January 1st, 2012 and December 31st, 2013 via electronic chart review. The subset for analysis were those who had an ECG both at time of fever and while afebrile (within 30 days of initial ECG). Temperature measurement was within 30 minutes of ECG. Actively paced patients were excluded. Univariate and multiple regression analysis were used to determine risk factors for QT derangement in patients with fever.Results: 2018 febrile visits occurred during the reviewed period, 181 of these patients went on to be included in the study. 54.1% of study subjects were female, and the average age was 68.9 years old. The etiology of fever was predominately infectious (69.6%), with community acquired pneumonia being the most frequent cause (24.3%). We found the median corrected QT interval to be significantly shorter in febrile as compared to afebrile patients [QTc = 388.7ms, (371.5-407.5) vs 406.7, (386.7-434.4); p < 0.001]. This difference was observed in both sexes. Males were found to be more likely to experience medication induced QTc prolongation [OR 5.35, 95% CI = 1.46 - 19.68; P < 0.05]. Two instances of Torsades de pointes were identified in our study, both occurring in males on QT prolonging medications.Conclusion: In an ED patient population, fever generally shortens the QT interval independent of sex. Prolongation of the QT interval during fever should thus increase clinical suspicion of congenital or acquired QT disorders. Additionally, males appear to be more susceptible to medication-induced derangements in the QT interval and may require more vigilant monitoring when treated with multiple QT prolonging medications.